Investigasi Hubungan Keragaman Gen Leptin Receptor (LEPR) dengan Karakteristik Karkas dan Kualitas Daging Domba - Azizah, D.; Noor, R. R.; Gunawan, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Improvement of meat quality plays important role for sheep meat producer and costumer market.Leptin Receptor (LEPR) gene is speculated has important role in carcass and meat quality. This studyaims to investigate the relationship between the LEPR gene variation with characteristics of carcassand meat quality in sheep. A total 50 rams consisted 20 of Javanese fat tailed (JFT), 10 of garutcomposite (GCS), 10 of compass agrinak (CAS), and 10 of barbados cross (BCS) were used in this study.Polymorphism of LEPR gene were performed by Polymerase Chain Reaction-Restriction FragmentLength Polymorphism (PCR-RFLP) with Acil as restriction enzyme. The results showed that of theamplification product was 432 bp. The result of polymorphism of LEPR gene were polymorphic withthird genotype including AA, AC, dan CC. The SNP of LEPR gene with genotype AA was associated(P<0.05) with carcass characteristics including empty body weight, cold carcass and with genotype ACon meat quality including tenderness. It could be concluded that the SNP g.40854778 A>C of LEPR genemay contribute to the characterictic carcass and meat quality in sheep